HUBUNGAN PENGETAHUAN DENGAN KELENGKAPAN PENGISIAN DOKUMENTASI ASUHAN KEPERAWATAN BERDASARKAN PENDEKATAN PROSES KEPERAWATAN MAHASISWA KEPERAWATAN SEMESTER VI STIKES BUANA HUSADA PONOROGO - Ani Rosita (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2022)
Knowledge is the process of finding information obtained by a person through various sensory organs. Knowledge in this case relates to the completeness of the nursing care documentation. The nursing process as a tool for nurses to carry out nursing care carried out on patients has an important meaning for both parties, namely nurses and clients. The purpose of this study is to analyze knowledge with completeness of filling in nursing care documentation based on the approach of the nursing process of nursing students in semester VI of STIKES Buana Husada Ponorogo. This study used a correlational design . The population in this study was all nursing students in semester VI of STIKES Buana Husada Ponorogo. The sample in this study was all 15 nursing students in semester VI of STIKES Buana Husada Ponorogo. The sampling technique is Total sampling. This study used the Spearman Rank statistical test with α = 0.05. The results of research from 15 respondents showed that student knowledge about nursing care documentation based on the nursing process approach was mostly good as many as 9 respondents (60%), students in documenting nursing care with the nursing process approach were mostly complete as many as 8 respondents (53.3%). There is a Relationship between Knowledge and Completeness of Filling in Nursing Care Documentation Based on the Nursing Process Approach of Nursing Students in Semester VI STIKES Buana Husada Ponorogo.with p value = 0.000 with α = 0.05 Respondents always update the latest science related to nursing care in order to be able to compile nursing care in a comprehensive and orderly manner in accordance with the development of science.